My Fate Is My Decision: The Differential Effects of Fate and Criticality of Decision Beliefs on Career Decision Making Self-Efficacy (European Journal of Behavioral Sciences, 2021)
Dysfunctional career decision-making beliefs (DCB) impede career decision making (CDM) process in several ways. This study proposes to delineate the profiles of two career-specific dysfunctional beliefs, fate (FB) and criticality of decision (CB) through their differential effects on career decision self-efficacy (CDSE) in undergraduate students. A sample of 157 undergraduate students (aged M = 21.07, SD = 1.78, 87.2% female) completed the fate and criticality beliefs subscales of Dysfunctional Career Decision-Making Beliefs Scale, Career Decision Self-Efficacy Scale and Career Satisfaction Scale. Two-step cluster analyses was provided for delineating the profiles of combined variables of fate and criticality beliefs. As the result, four clusters emerged: criticality of decision beliefs (CB), fate beliefs (FB), negotiable fate beliefs (NFB) and no dysfunctional beliefs (NB) group. Clusters did not differ in terms of gender, age, GPA or career satisfaction. The profiles of DCB did not differ in CDSE; statistically significant group differences were only found for career goal selection. More specifically, FB group showed significantly less self-efficacy in setting their career goals as compared to CB or NFB groups. Results indicate that dysfunctional fate beliefs are associated with low perceived self-efficacy regarding the selection of goals in the process of career decision-making. However, the effect of FBs can be buffered by CBs, dysfunctional of their kind, suggesting that negotiable FBs have a more favourable effect on career related goal selection self-efficacy as they draw back the process of CDM under personal influence.